Alkoholizm jako przyczyna rozwodu - Ogrodnik, Agnieszka (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostępne wyłącznie w języku angielskim: One of the main reasons for divorces in Poland is alcoholism. Approximately 23 % of divorces are caused by an alcoholic husband or an alcoholic wife. Alcoholism as a reason of divorce has many specific features. First of all an alcoholic husband or an alcoholic wife is to blame for a divorce, although alcoholism is a disease. It is caused by many very negative consequences of alcoholism, like aggression, neglecting a family or unfaithfulness. Secondly, alcoholism has a really bad influence on marriage, especially destroys relations between a husband and a wife. It also has a very bad influence on a child, who groves up in such a family. An alcoholic mother or an alcoholic father destroys not only the childhood of their children, but also their future life. Approximately 1/3 of them divorce.